A -regulating single-nucleotide polymorphism as a predictive marker candidate for platinum-based chemotherapy in gastrointestinal cancers - Takahiro Mori; Kazuko Ueno; Masao Nagasaki; Koichi Matsuda (Therapeutic Advances in Medical Oncology, 2025)
Background: Platinum-based compounds have been instrumental in clinical oncology, underscoring the critical need to identify predictive biomarkers for these agents to advance personalized medicine. Objectives: This study aimed to identify predictive biomarkers for platinum-based chemotherapies in gastrointestinal cancers. Design: This study was designed to explore candidate single-nucleotide polymorphisms (SNPs) through a genome-wide association study (GWAS), followed by re-evaluation using external nationwide cohorts. Subsequently, the biological functions of the selected SNPs were analyzed utilizing the online multi-omics databases. Methods: First, we conducted a GWAS in a discovery cohort of esophageal cancer (EC) patients undergoing platinum-based chemoradiation therapy, followed by Cox proportional-hazards analyses for overall survival and progression-free survival. Potential candidate polymorphisms identified in the discovery phase were validated in an external cohort derived from the nationwide BioBank Japan (BBJ). Results: Validation analysis revealed a significant association between the T allele of rs12876842 and tumor control rates in a gastric cancer cohort ( p  = 0.006). In other BBJ cohorts, including the chemoradiotherapy-treated BBJ-EC cohort, the odds ratio trends were consistent with the hazard ratios observed in the discovery cohort, indicating concordance of the risk allele across cancer types, although statistical significance was not reached. Analysis of online databases suggests that the C allele, identified as a risk allele, exhibits higher binding affinity to KLF4, while POLR1D, a downstream target of KLF4, may contribute to adverse prognostic signatures across multiple cancers. Besides, a significant association between genotype of rs12876842 and POLR1D expression in the gastroesophageal junction is confirmed in Genome Tissue Expression ( p  = 0.0000113), and prior studies have linked POLR1D expression with disease progression, neoplastic transformation, chemotherapy resistance, and poor clinical outcomes in various malignancies. Conclusion: Given the centrality of platinum-based drugs in cancer therapy, our findings align with biochemical evidence and prior literature, highlighting rs12876842 as a promising prognostic biomarker.